Assessment of ecotoxicity effects of aspirin on non-target organism (Daphnia magna) via analysis of the responses of oxidative stress, DNA methylation-related genes expressions and life traits changes - Cuiping, He (Ecotoxicology (London, England), 2023)
© 2023. The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.